2018
DOI: 10.1039/c8ce01352g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of size-controlled UO2 microspheres from the hydrothermal conversion of U(iv) aspartate

Abstract: A wet chemistry route towards UO2 spherical particles was designed through the hydrothermal conversion of uranium(iv) aspartate. A multi-parametric study led us to point out the conditions leading to monodisperse and size-controlled particles in the 400–2500 nm range. This simple protocol paves the way to applications in various scientific areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 43 publications
6
30
0
Order By: Relevance
“…Indeed, after the initial decomposition of the oxalate moieties, the formation of the oxide was likely to occur through the formation of hydroxides, which further rapidly aged to form UO2+x.nH2O. This mechanism was already depicted by several authors 14,39 . Rai et al already reported that such reaction operated at room temperature for pH > 2 40 , while the solubility of amorphous UO2 did not sustain important variation up to 300°C 13 .…”
Section: Effect Of Temperaturementioning
confidence: 72%
“…Indeed, after the initial decomposition of the oxalate moieties, the formation of the oxide was likely to occur through the formation of hydroxides, which further rapidly aged to form UO2+x.nH2O. This mechanism was already depicted by several authors 14,39 . Rai et al already reported that such reaction operated at room temperature for pH > 2 40 , while the solubility of amorphous UO2 did not sustain important variation up to 300°C 13 .…”
Section: Effect Of Temperaturementioning
confidence: 72%
“…Synthetic UO 2 microspheres (ICSM particles) were analyzed by SEM/EDX in order to characterize their porosity and size distribution. The SEM characterization was carried out on particles deposited on a graphite disk without collodion, as this non‐conductive organic polymer degrades the quality of the SEM pictures.…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of the ICSM particles was based on the initial precipitation of U(IV) aspartate from a mixture of tetravalent uranium in hydrochloric media and aspartic acid. 32 This precursor was then processed under hydrothermal conditions (T = 160°C, t = 30 h) in order to achieve the conversion towards UO 2 and to recover spherical particles. Finally, the resulting powder after this treatment was heated at 600°C under an Ar/H 2 -2% atmosphere in order to eliminate residual organics and water.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Both thermal ionization (TIMS) and secondary ion mass spectrometry (SIMS) are primary particle characterization tools for these analyses, but representative particulate (reference and proficiency testing) materials have been historically limited and/or unavailable. This material need is recognized by the IAEA as urgent; with our team and others pursuing the R&D required to reproducibly produce single and mixed element reference particulates [2][3][4][5]. Initial efforts focused on U/Ce as a convenient test surrogate for U/Th and U/Pu materials.…”
mentioning
confidence: 99%